Experiences with Technology Amongst an International Sample of Older Adults: Results from a Qualitative Interpretive Meta-Synthesis. (27th February 2021) - Miller, Vivian J; Roark, Erin M; Fields, Noelle L; Cronley, Courtney
Abstract: Identifying and implementing effective strategies to combat social exclusion and isolation is critical, given that eradicating social isolation has been identified as one of the social work profession's main goals. Training older adults to use information and communications technology (ICT) effectively may be an appropriate intervention to combat and mitigate the negative impacts of social isolation within the aging population. ICT has demonstrated promise with older adults, with research demonstrating that older adults with higher technology use report better self-reported physical health and subjective well-being. Given this promise, the authors of this study seek to create more nuanced understanding of the experience of ICT usage, as told by an international sample of older adults using a qualitative interpretive meta-synthesis (QIMS). Using the QIMS methodology paired with phenomenological reduction, the authors synthesised nine ( N  =   9) qualitative studies through the lens of the World Health Organization's age-friendly domains. This process resulted in three overarching themes that describe older adults' experiences engaging with technology: 'desire for empowerment', 'connection' and 'aging well'. Findings from this study highlight overall benefits of technology use among older adults aging in the community. This study concludes with implications for social work research and practice.